The Effect of Social Support and Interest in Online Learning on Student Achievement Motivation - Masduki Ahmad; Heni Rochimah; Nurul Hasanah Fajaria (AL-ISHLAH: Jurnal Pendidikan, 2022)
Changes in the order of learning, which are all face-to-face to online, certainly have many consequences, one of which is the aspect of achievement motivation. This study determines how social support and interest in online learning influence student achievement motivation. This study uses a quantitative approach by distributing online questionnaires. The population of this study is 2200 students using the slovin formula (5%), so the sample in this study is 338 students. Data analysis techniques include multiple linear regression with t-test and F-test as hypothesis testing. The calculation results of the data obtained by the multiple linear regression equation are Y = 41.561 + 0.471 - 0.189, with a large influence on social support and online learning interest with the student achievement motivation variable, namely 53.6%. The results of the hypothesis test obtained are tcount for social support variable 10,600 ttable (1,967), count for online learning interest variable 5,161 ttable (1,967. Simultaneously, Fount 194,868 Ftable 3.02. Based on these results, it is stated that the variables of social support and interest are online learning has a positive and significant effect on students' achievement motivation variables.